Alquilação redutiva da quitosana a partir do glutaraldeído e 3-amino-1-pr - Alves, Keila dos Santos (2008)
Chitosan derivatives were prepared by reductive alkylation using glutaraldehyde and 3-amino-1-propanol. The reducing agent used was the sodium borohydride. Tests of solubility, stability and viscosity were performed in order to evaluate these parameters effects in the reaction conditions (molar ratio of the reactants and presence of nitrogen in the reaction system). The molecular structure of commercial chitosan was determined by infrared (IR) and hydrogen nuclear magnetic resonance spectroscopy (1H NMR). The intrinsic viscosity and average molecular weight of the chitosan were determined by viscosimetry in 0.3 M acetic acid aqueous solution 0.2 M sodium acetate at 25 ºC. The derivatives of chitosan soluble in aqueous acidic medium were characterized by 1H NMR. The rheological behavior of the chitosan and of the derivative of chitosan (sample QV), which presented the largest viscosity, were studied as a function of polymer concentration, temperature and ionic strength of the medium. The results of characterization of the commercial chitosan (the degree of deacetylation obtained equal 78.45 %) used in this work confirmed a sample of low molar weight (Mv = 3.57 x 104 g/mol) and low viscosity (intrinsic viscosity = 213.56 mL/g). The chemical modification of the chitosan resulted in derivatives with thickening action. The spectra of 1H NMR of the soluble derivatives in acid aqueous medium suggested the presence of hydrophobic groups grafted into chitosan in function of the chemical modification. The solubility of the derivatives of chitosan in 0.25 M acetic acid aqueous solution decreased with increase of the molar ratio of the glutaraldehyde and 3-amino-1-propanol in relation to the chitosan. The presence of nitrogen and larger amount of reducing agent in reaction system contributed to the increase of the solubility, the stability and the viscosity of the systems. The viscosity of the polymeric suspensions in function of the shear rate increased significantly with polymer concentration, suggesting the formation of strong intermolecular associations. The chitosan presented pseudoplastic behavior with the increase in polymer concentration at a low shear rate. The derivative QV presented pseudoplastic behavior at all concentrations used and in a large range of shear rate. The viscosity of chitosan in solution decreased with an increase of the temperature and with the presence of salt. However, there was an increase of the viscosity of the chitosan solution at higher temperature (65 ºC) and ionic strength of the medium which were promoted by hydrophobic associating of the acetamide groups. The solutions of the chitosan derivatives (sample QV) were significantly more viscous than chitosan solution and showed higher thermal stability in the presence of salt as a function of the hydrophobic groups grafted into chitosan backbone